(3JWhQ eYGjjQ GdJObjb h GdJCcjO GdOhdjI h bhGYO GNdGbjGJ GdegfIs - (3GMeO Mdej(B, (3LeYIs ((3YeGf(B:s (3OGQ UaGA ddfTQ(B,s, 2009)
(3GdJObjb GdHjFj (B-(3eQGYGI Yed GdJObjb GdOGNdj (B-(3GdGSJaGOI ef Yed eObb BNQ (B-(3JObjb GdefTBJ GdUZjQIs
(3SdSdI GdcJH GdegfjIs
Keywords: (3GNdGbjGJ GdegfIs; (3GdeMGSHIs; (3GdeMGSHI GdeGdjIs; (3GdeMGSHhfs; (3JObjb GdMSGHGJs